Polydimethylsiloxane–graphene oxide composite improving performance by ion beam irradiation. (11th October 2020) - Cutroneo, Mariapompea; Havránek, Vladimír; Torrisi, Alfio; Mackova, Anna; Malinsky, Petr; Slepicka, Petr; Sofer, Zdenek; Torrisi, Lorenzo
Abstract : A hybrid film consisting of graphene oxide covered with poly(dimethylsiloxane) was prepared via spin coater and followed by thermal annealing to improve the bond strength of the polymerized systems. Direct patterning on both graphene oxide and hybrid graphene oxide–poly(dimethylsiloxane) foils by ion microbeam was performed to induce localized reduction in the ion irradiated material. It is well established that the ion irradiation of graphene oxide induces modifications in its electrical, mechanical, and optical properties and disorder in the carbon crystal structure and defect production. The presence of poly(dimethylsiloxane) can be useful as it confers flexibility to the produced pattern and oxygen permeability from the graphene oxide surface. Rutherford backscattered spectroscopy and elastic recoil detection analysis were performed to evaluate the compositional changes in the composite. Atomic force microscopy studied the pattern fidelity. The electrical conductivity of the hybrid material was used to evaluate the changes induced during the proton irradiation of the material.